TEOLOGI KERUKUNAN DALAM KONTEKS PLURALITAS AGAMA - Ahmad, Muhammad Kursani (Jurnal Ilmiah Ilmu Ushuluddin, 2010)
The plurality of religion is undeniable and it should be theologically un-derstood as civilized relations among different religions and beliefs. Theo-logical dialogue is needed to establish mutual understanding and peacefulrelations among religions. This theology is called âtheology of harmonyâ inwhich one can put his/her faith in the same line with faith of other people.